Musykilatu al Mudarrisi fī Ta’līmi al Lughati al ‘Arabiyyati bi al Madrasati al ‘Āliyati al Islāmiyyati al Ḥukūmiyyati Jāmbi - Prihartini, Yogia; Wahyudi, Hakmi (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2021)
The teaching profession is considered one of the important professions in any civilized people, and teaching Arabic in a non-Arab environment, as is the case in Indonesia, requires rehabilitation, training, and development. It starts from the previous stage of teaching in the Arabic language departments, whether in the College of Education or the College of Arts in Indonesian universities. During the teacher's work period, he continues to teach this noble language. The reality of teaching Arabic in Indonesia faces many problems, the most important of which are the linguistic weakness of Arabic language learners, the difficulty of creating an Arabic environment, the lack of books and literature in teaching Arabic, the lack of educational aids to teach Arabic in the existing curricula. The teacher is the reservation on the basis in any educational process. The existence of a good curriculum will be sterile without the availability of a skilled teacher, and teaching Arabic to non-native speakers is an area that requires linguistic, professional, psychological, and social capabilities that are rarely available to one person from the teachers, as language teachers Arabic in Islamic schools, and even in Islamic universities is often either a specialist in teaching a language who is not good at it, or a glorified one for a language who is not specialized in teaching it to non-native speakers, and we rarely see the presence of a linguistically glorified Arabic teacher who is familiar with the methods of teaching Arabic.